Sex-differences in endotoxemia and trimethylamine N-oxide according to the diet and type 2 diabetes status in coronary heart disease patients: from the CORDIOPREV study - Garcia-Fernandez, Helena; Arenas-Montes, Javier; Gutierrez-Mariscal, Francisco M.; Alcala-Diaz, Juan F.; Allais, Alisa; Arenas-de Larriva, Antonio P.; Luque-Cordoba, Diego; Torres-Peña, Jose D.; Romero-Cabrera, Juan L.; Luque, Raul M.; Priego-Capote, Feliciano; Delgado-Lista, Javier; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiovascular disease (CVD) develops in men earlier in life but CVD women have a higher risk of cardiovascular mortality than CVD men. In addition, co-occurrence with type 2 diabetes mellitus (T2DM) increases CVD risk. We aimed to evaluate sex differences in endotoxemia and trimethylamine N-oxide (TMAO) plasma levels, in co-occurrence with T2DM in coronary heart disease (CHD) patients, and their potential sex-specific modulation by the consumption of healthy diets.MethodsThis study was carried out within the framework of the CORDIOPREV study, a clinical trial which included 1,002 (827 men and 175 women) with CHD, of whom 462 had no T2DM, 350 had T2DM, and 190 were newly diagnosed with T2DM at recruitment. Plasma lipopolysaccharide (LPS) was measured by LAL colorimetric assay and TMAO by HPLC. Intima-media thickness of both common carotid arteries (IMT-CC) and carotid plaques were assessed ultrasonically.ResultsLPS and TMAO plasma levels were lower in CHD non-T2DM women than CHD non-T2DM men (both, P-value <0.05), whereas no sex differences were observed in CHD T2DM patients, or CHD newly-diagnosed T2DM patients. These sex differences were consistent with lower IMT-CC and a smaller number of plaques in CHD non-T2DM women than in CHD non-T2DM men, with no sex differences found in CHD T2DM patients, or CHD newly-diagnosed T2DM patients. In contrast, C-reactive protein plasma levels were higher in CHD T2DM women than CHD T2DM men (P = 0.012 and P = 0.001, respectively), with no sex differences found in CHD non-T2DM patients. Both, LF and Med diets reduced the LPS plasma levels in CHD men and women newly diagnosed with T2DM.ConclusionsOur results suggest that the sex differences in CHD patients are influenced by the presence of T2DM. Moreover, our results also suggest that the cardiovascular risk associated to T2DM, in co-occurrence with CVD, is higher in women than in men.